Sikap Karakter untuk Generasi Muda Berkelanjutan di Kota Tegal - Tity Kusrina; Suwandono; R Samidi (Cakrawala: Jurnal Pendidikan, 2021)
This research aims to arrange the stages to develop character attitudes and build the spirit of the younger generation to be sustainable. This study uses descriptive qualitative methods and phenomology with the aim of deeper understand into the data with the consideration that the participants studied are easier when dealing with reality and the close emotional relationship between the researcher and the respondent is another consideration. Data collection techniques by means of interviews and observations. The results of this study indicate that the process of growing character attitudes can go through 4 stages, namely (1) Socialization (2) Technical Assistance, (3) Place Mapping, (4) Planning